Answer: C) Changing one or more properties of a sine wave in response to data.
Step-by-step explanation:
Modulation is primarily used in telecommunications sector. It the process by which data is transmitted via electrical signals. It is the process of imposing an input signal on to a wave carrier. It is the pillar of data communication that enables the use information carriers of signals that are electrical and optical. Altering the carrier/ periodic waveform results in Modulation. The amplitude frequency and phase are conveyed. There are different types of Modulation which includes: amplitude Modulation, frequency Modulation, and phase Modulation.
He doesn’t have enough, he has 19/8 and needs 20/8 for 10 burgers, he’s missing 1/8 :)
Well, "minus 6 x cubed minus y squared minus 3 x y" translates to:
![-6x^{2} -y^{2} -3xy](https://tex.z-dn.net/?f=-6x%5E%7B2%7D%20-y%5E%7B2%7D%20-3xy)
Then, if we insert the values for x and y, we get:
![-6(-2)^{2} -(4)^{2} -3(-2)(4)](https://tex.z-dn.net/?f=-6%28-2%29%5E%7B2%7D%20-%284%29%5E%7B2%7D%20-3%28-2%29%284%29)
When we distribute and multiply:
![144-16-24](https://tex.z-dn.net/?f=144-16-24)
And once we combine like terms:
104<em> is the answer</em>
Answer:
Yumiko should multiply the other equation by 3.
If she adds the two equations she would be left with the variable 'x'.
Step-by-step explanation:
Given the two equations are as follows:
![$ 2x - 3y = 12 \hspace{5mm} \hdots (1) $](https://tex.z-dn.net/?f=%24%202x%20-%203y%20%3D%2012%20%5Chspace%7B5mm%7D%20%5Chdots%20%281%29%20%24)
![$ 5x + 6y = 18 \hspace{5mm} \hdots (2) $](https://tex.z-dn.net/?f=%24%205x%20%2B%206y%20%3D%2018%20%5Chspace%7B5mm%7D%20%5Chdots%20%282%29%20%24)
It is given that she multiplies the first equation by 6. Therefore, (1) becomes
![$ 12x - 18y = 72 \hspace{15mm} \hdots (a) $](https://tex.z-dn.net/?f=%24%2012x%20-%2018y%20%3D%2072%20%5Chspace%7B15mm%7D%20%5Chdots%20%28a%29%20%24)
Now, note that the sign of the variable 'y' is negative. So, if we make the co-effecient of 'y' equal in both the cases, add them it would result in the elimination of the variable 'y'.
The co-effecient of y in Equation (2) is 6. To make it 18 like it is in Equation (1), we multiply throughout by 3.
Therefore, Equation (2) becomes:
![$ 15x + 18y = 54 \hspace{5mm} \hdots (b) $](https://tex.z-dn.net/?f=%24%2015x%20%2B%2018y%20%3D%2054%20%5Chspace%7B5mm%7D%20%5Chdots%20%28b%29%20%24)
Now, we add Equation (a) and Equation (b).
![$ \implies 12x - 18y + 15x + 18y = 72 + 54 $](https://tex.z-dn.net/?f=%24%20%5Cimplies%2012x%20-%2018y%20%2B%2015x%20%2B%2018y%20%3D%2072%20%2B%2054%20%24)
![$ \implies 27x = 126 $](https://tex.z-dn.net/?f=%24%20%5Cimplies%2027x%20%3D%20126%20%24)
Factor: 3
Equation: 27x = 126
Answer:
4n+2
Step-by-step explanation:
- add all sides =9n+3
- 3n+2+2n-1=9n+3
- add liketerms 5n+1=9n+3
- put liketerms together 9n-5n+3-1
- ans hence is 4n+2